Analysis of public policies and early childhood education in the Dominican Republic - Guzmán-Taveras , Lourdes Natalia (2022)
Since 2013, the Dominican Republic declared early childhood of the highest interest and new comprehensive care programs have emerged. This article presents research that answers the question: What is the alignment between evidence on early childhood education best practices with the Dominican Republic's education policy and its implementation? Information was triangulated across a) a conceptual framework of evidence; b) documentary analysis of policies and their implementation; and c) interviews with stakeholders. The results show variability between compulsory education and other modalities. There is a need to improve the alignment of institutional coordination, coverage of care, entry of teaching staff, and infrastructure and security, with what the evidence recommends.